Molecular Detection of Some β-lactamases Genes in Uropathogenic Escherichia coli - H. Hammadi, Ali; N. Yaseen, Najlaa; J. F. Al-Mathkhury, Harith (Iraqi Journal of Science, 2023)
Around fifty Escherichia coli isolates were isolated from sixty midstream urine specimens collected from patients visiting hospitals in Baghdad city. Approximately, 52% of all isolates were identified as extended spectrum beta lactamases (ESBL) producer. Results demonstrated that 92% of these isolates were sensitive to carbapenems. Only four β-lactamase coding genes were detected; blaTEM, blaPER, blaVIM and blaCTX-M-2. As a conclusion, this work revealed that local E. coli isolates harboured ESBL coding genes which may contribute in its pathogenicity.